1991
DOI: 10.1177/026921639100500212
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Hydration or Feeding in Advanced Disease — a Flow Diagram

Abstract: Reduced hydration and feeding is here defined as a reduction in the intake and quality of drink or food sufficient to produce weight loss, nutritional deficiency, or both. Advanced disease includes any progressive disease process in which the prognosis is limited. This flow diagram outlines the management of reversible and irreversible causes of reduced intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Refusal of food and fluid by a dying person is a common occurrence, particularly as the body slowly shuts down, and this may be the evidence signifying an actively dying process rather than starvation (Ijaopo & Ijaopo, 2019). Previous studies have argued that dehydration is not distressing, rather, may provide comfort to the dying patient in reducing death rattle (Regnard & Mannix, 1991). One recently published multicenter prospective observational study showed that giving a dying person a higher amount of fluids, in excess of 250 mL/ day, during 48 to 25 hr before death may be associated with the occurrence of terminal restlessness in the last 24 hr of life (Lokker et al, 2021).…”
Section: Decreased Food Intake and Impaired Hydrationmentioning
confidence: 99%
“…Refusal of food and fluid by a dying person is a common occurrence, particularly as the body slowly shuts down, and this may be the evidence signifying an actively dying process rather than starvation (Ijaopo & Ijaopo, 2019). Previous studies have argued that dehydration is not distressing, rather, may provide comfort to the dying patient in reducing death rattle (Regnard & Mannix, 1991). One recently published multicenter prospective observational study showed that giving a dying person a higher amount of fluids, in excess of 250 mL/ day, during 48 to 25 hr before death may be associated with the occurrence of terminal restlessness in the last 24 hr of life (Lokker et al, 2021).…”
Section: Decreased Food Intake and Impaired Hydrationmentioning
confidence: 99%